Ultrasound versus magnetic resonance imaging for calculating total kidney volume in patients with ADPKD: a real‑world data analysis - Fernandez, Juan M.; Hernández‑Socorro, Carmen Rosa; Robador, Lucas Omar; Rodríguez‑Esparragón, Francisco; Medina‑García, Daniela; Quevedo‑Reina, Juan Carlos; Lorenzo‑Medina, Mercedes; Oliva‑Dámaso, Elena; Pérez‑Borges, Patricia; Rodríguez‑Perez, José C. (The Ultrasound Journal, 2025)
Background and objectives: This study aimed to compare Total kidney volume (TKV) measurements using US-ellipsoid (US-EL) and MRI-ellipsoid (MRI-EL) in patients with autosomal-dominant-polycystic-kidney-disease (ADPKD). It also evaluated whether the agreement between right (RKV) and left (LKV) kidney volume measurements differed.Methods: Retrospective analysis of a prospective data-base that included consecutive patients diagnosed with ADPKD. Total kidney volumes by 3D-US-EL were compared with those by MRI-EL. Bland–Altman-plots, Passing–Bablok-regression, and the concordance-correlation-coefficient (CCC) were used to compare right (RKV), left (LKV), and TKV measurements.Results: Thirty-two ADPKD patients, 14(43.7%) women, were included. Mean measured (mGFR) and estimated (eGFR) glomerular-filtration-rate (GFR) were 86.5 ± 23.9 mL/min and 78.9 ± 23.6 mL/min, respectively. Compared with MRI-EL, TKV (Mean difference: − 85.9 ± 825.6 mL; 95%CI − 498.5 to 326.7 mL; p = 0.6787), RKV (Mean difference: − 58.5 ± 507.7 mL; 95%CI − 312.2 to 195.2 mL; p = 0.6466), and LKV (Mean difference: − 27.4 ± 413.5 mL; 95%CI − 234.1 to 179.2 mL; p = 0.7918) were lower with US-EL than with MRI-EL, although without significant differences. According to Passing and Bablok-regression analysis, the Spearman correlation-coefficient was 0.96 (95%CI 0.92 to 0.98); 0.91 (95%CI 0.82 to 0.96), and 0.94 (95%CI 0.87 to 0.97) in the RKV, LKV, and TKV, respectively; p